Evaluation of Equality Education Program: Promoting Access and Quality of Learning in Community Learning Center - Nining Hardiyanti; Imam Shofwan; Sachin Gupta (Edukasi, 2025)
The purpose of this study is to evaluate the equality program at PKMB Tunas Mualia Semarang. This study uses a descriptive qualitative approach research design. This study uses the evaluation of the CIPP model including aspects (Context) related to the analysis of program needs and program objectives, (Input) related to the characteristics of trainees, instructor qualifications, training curriculum, funding, and training facilities and infrastructure, (Process) related to training schedules, trainee activities, instructor activities, learning strategies, and obstacles in implementation, and (Product) related to the results and benefits as well as graduation of trainees. Research data was collected through observation, interviews, and documentation. The validity technique used in this study is triangulation of methods and sources. Based on the results of the study, the evaluation of the CIPP program in the Equality Education Program at PKBM Tunas Mulia Semarang showed significant effectiveness. Context evaluation reveals that the establishment of PKBM is based on the low level of education of the community. This program has succeeded in increasing educational awareness through the approach of local figures, but it is constrained by students' economic problems that cause difficulties in paying contributions, so PKBM needs an innovative financing strategy. Input evaluation shows that students are of productive age and the quality of teaching is guaranteed by qualified tutors, with a curriculum that refers to the Independent Curriculum. Process evaluations highlight the flexibility of learning schedules and participants' involvement in various activities. Product evaluations showed significant social impact, with many participants graduating from various levels. Overall, PKBM Tunas Mulia has successfully implemented an effective equality education program, although it needs to adapt to economic challenges.